Thesaurus and subject heading lists as Linked Data - Everton Rodrigues Barbosa; Moisés Lima Dutra; Angel Freddy Godoy Viera; Douglas Dyllon Jeronimo de Macedo (Transinformação, 2021)
Abstract Most libraries put a lot of effort into developing subject headings or thesauri, which are used to index and retrieve information. Nevertheless, in the library field, controlled vocabularies are associated to authority records as authority files. In order to become findable by search engines, these authority files should be modelled on semantic vocabularies. This research proposes an authority-record conversion process for publishing thesauri and subject headings as linked data, by using the Simple Knowledge Organization Systems data model. To this purpose, we undertook a bibliographic and documentary research on the World Wide Web Consortium recommendation guidelines, which were used to produce a set of procedures and technologies to support the conversion proposal. This research provides evidences that controlled vocabularies are an important resource for improving information retrieval on the web. The proposed conversion process works as a quick guide for controlled vocabulary integration and reuse among users and systems on the linked data environment. Although the proposal was originally intended for a library setting, it can be applied and tested in another type of institution, such as documentation centres, museums, or cultural heritage archives. It can also be used in other linked open data projects.